1988
DOI: 10.7124/bc.00020d
|View full text |Cite
|
Sign up to set email alerts
|

Measurement ob DNA-protein binding constants by means of chromatograph «Milichrom» —computer complex

Abstract: Thermal denaturation of distamicin A-DNA complexes as followed hyperchromic spectra // Biophys. Chem.-1980.-11, N 2.-P. 233-237. 11. Об особенностях перехода спираль-клубок ДНК в области инверсии относительной стабильности GC-и АТ-пар, обусловленной ионами Си 2 + и Мп 2+ / Ю.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Binding of proteins with DNA in aqueous media has been extensively studied in the last few decades, and attempts have been made to relate binding processes with the control of genetic and other biological properties. Binding of the basic proteins histones and many acidic proteins present in chromosomes with DNA in aqueous media has been investigated by several workers with interesting results. Calorimetric studies on polypeptide−DNA systems have revealed that the formation of macromolecular complexes is an entropy-driven process. Using a gel chromatography technique, DNA−protein binding constants in aqueous media have been evaluated. Cross-linking between DNA and protein in aqueous media with application of UV laser and other techniques has been recently reported by several workers. , Protein−protein and protein−nucleic acid interactions occuring in λ repressor−operator systems have been recently reviewed by Roy .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of proteins with DNA in aqueous media has been extensively studied in the last few decades, and attempts have been made to relate binding processes with the control of genetic and other biological properties. Binding of the basic proteins histones and many acidic proteins present in chromosomes with DNA in aqueous media has been investigated by several workers with interesting results. Calorimetric studies on polypeptide−DNA systems have revealed that the formation of macromolecular complexes is an entropy-driven process. Using a gel chromatography technique, DNA−protein binding constants in aqueous media have been evaluated. Cross-linking between DNA and protein in aqueous media with application of UV laser and other techniques has been recently reported by several workers. , Protein−protein and protein−nucleic acid interactions occuring in λ repressor−operator systems have been recently reviewed by Roy .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Calorimetric studies 11 on polypeptide-DNA systems have revealed that the formation of macromolecular complexes is an entropy-driven process. Using a gel chromatography technique, 12 DNA-protein binding constants in aqueous media have been evaluated. Cross-linking between DNA and protein in aqueous media with application of UV laser and other techniques has been recently reported by several workers.…”
Section: Introductionmentioning
confidence: 99%